High-entropy rare earth ceramic powder as well as rapid preparation method and application thereof
The preparation of high-entropy rare earth ceramic powder by laser radiation heating method is solved, and the problems of long synthesis cycle, small component space and uneven element distribution in the prior art are solved, and the rapid and efficient preparation of high-entropy ceramic powder is achieved, which is suitable for Thermal end components of aerospace engines.
Patent Information
- Application Number
- CN202411399817.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing preparation methods for high-entropy rare earth ceramic powders have problems such as long synthesis cycle, small synthesis component space, uneven element distribution and impurity-containing phases. They also lack simple, fast and efficient high-throughput screening methods, which limits the material's Development and application.
The rare earth oxide powder is mixed evenly with HfO2, ZrO2, Ta2O5 and SiO2 powders by laser radiation heating, and high-entropy rare earth ceramic powder is prepared by laser heating to achieve rapid and efficient synthesis.
It has achieved rapid preparation of high-entropy rare earth ceramic powder, with excellent characteristics such as uniform element distribution, no impurity phase, and large synthesis component space. It is suitable for use in hot-end components of aerospace engines and has broad application prospects.
Smart Images

Figure CN119390447A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high entropy ceramic materials, and in particular to a high entropy rare earth ceramic powder and a rapid preparation method and application thereof. Background Art
[0002] High-entropy rare earth oxides are considered to be a kind of inorganic compound solid solution, in which one or more Wyckoff sites are occupied by 4 or more rare earth elements, and each rare earth element accounts for 5at.% to 35at.%. Due to its unlimited possibilities of composition design and performance regulation, it has attracted widespread attention from researchers. So far, a variety of high-entropy rare earth oxide systems including high-entropy rare earth hafniumate ceramics, high-entropy rare earth zirconate ceramics, high-entropy rare earth tantalate ceramics, high-entropy rare earth monosilicate ceramics, high-entropy rare earth disilicate ceramics, etc. have been developed one after another. High-entropy rare earth hafniumate ceramics, high-entropy rare earth zirconate ceramics and high-entropy rare earth tantalate ceramics have a thermal expansion coefficient that matches that of nickel-based high-temperature alloys, and have good high-temperature phase stability and outstanding thermal stress resistance, and are widely used in thermal barrier coatings. High-entropy rare earth monosilicate ceramics and high-entropy rare earth disilicate ceramics have excellent physical and chemical compatibility with silicon-based ceramic matrices, good high-temperature phase stability, outstanding resistance to CMAS, and excellent resistance to water and oxygen corrosion. They are considered to be the best candidate materials for the next generation of environmental barrier coatings and have very broad application prospects in the hot end components of aerospace engines.
[0003] However, there are few reports on the preparation methods of high-entropy rare earth ceramic powders, and their synthesis is mainly achieved through solid-phase reaction method. Solid-phase reaction method has the advantages of low cost, high yield, simple preparation process, etc., and is currently the most commonly used method for synthesizing high-entropy rare earth ceramic powders (Equiatomic quaternary (Y 1 / 4 Ho 1 / 4 Er 1 / 4 Yb 1 / 4 )2SiO5 silicate:Aperspective multifunctional thermal and environmental barrier coating material, Xiaomin Ren, Zhilin Tian, Jie Zhang, JingyangWang. Scripta Materialia, 2019, 168: 47-5; High-entropy ferroelastic rare-earth tantalite ceramic: (Y 0.2 Ce 0.2 Sm 0.2 G 0.2 Dy 0.2)TaO4, Jun Wang, Fushuo Wu, Ruoan Zou, Yueshu Wu, Mengdi Gan, Jing Feng, Xiaoyu Chong. Journal of American ceramic society, 2021, 104: 5873-5882), but this method has problems such as long synthesis cycle (3 to 4 days), small space for synthesizable components, uneven element distribution, and impurity phase. In addition, due to the huge space of high-entropy components, there is currently a lack of simple, fast and efficient high-throughput screening methods, which seriously limits the development and practical application of high-performance high-entropy rare earth ceramic materials.
[0004] Therefore, it is of great significance to develop a universal, simple, fast, efficient method for preparing high-entropy rare earth ceramic powders that can be used for high-throughput screening of materials, and to prepare high-entropy rare earth ceramic powders with uniform element distribution, no impurity phases, and a large space for synthesized components. Summary of the invention
[0005] The purpose of the present invention is to provide a high-entropy rare earth ceramic powder and a rapid preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A method for rapidly preparing high entropy rare earth ceramic powder comprises the following steps:
[0008] 1) uniformly mixing rare earth oxide powder with one of HfO2 powder, ZrO2 powder, Ta2O5 powder and SiO2 powder to obtain a mixed powder;
[0009] 2) The mixed powder is subjected to laser radiation heating to obtain high entropy rare earth ceramic powder.
[0010] Preferably, the rare earth oxide powder in step 1) is composed of at least four of Sc2O3 powder, Y2O3 powder, La2O3 powder, Nd2O3 powder, Sm2O3 powder, Eu2O3 powder, Gd2O3 powder, Dy2O3 powder, Ho2O3 powder, Er2O3 powder, Tm2O3 powder, Yb2O3 powder, and Lu2O3 powder in an equal molar ratio.
[0011] Preferably, the particle sizes of the rare earth oxide powder, HfO2 powder, ZrO2 powder, Ta2O5 powder and SiO2 powder in step 1) are all 1 μm to 3 μm, and the purity is ≥99.9%.
[0012] Preferably, in step 1), the molar ratio of the rare earth oxide powder to the HfO2 powder is 1:2.0-2.2.
[0013] Preferably, in step 1), the molar ratio of the rare earth oxide powder to the ZrO2 powder is 1:2.0-2.2.
[0014] Preferably, in step 1), the molar ratio of the rare earth oxide powder to the Ta2O5 powder is 1:1.0 to 1.1.
[0015] Preferably, the molar ratio of the rare earth oxide powder and the SiO2 powder in step 1) is 1:1.0-1.1 or 1:2.0-2.2. The molar ratio of the rare earth oxide powder and the SiO2 powder is controlled to be 1:1.0-1.1 to obtain a high-entropy rare earth monosilicate ceramic powder; the molar ratio of the rare earth oxide powder and the SiO2 powder is controlled to be 1:2.0-2.2 to obtain a high-entropy rare earth disilicate ceramic powder.
[0016] Preferably, the specific operations of mixing in step 1) include wet ball milling, drying and grinding.
[0017] Preferably, the process parameters of the wet ball milling include: the ball milling medium is anhydrous ethanol, the ball milling equipment is a planetary ball mill, the weight ratio of the powder raw material, ZrO2 balls and anhydrous ethanol is 1:1.8~2.2:1.0~1.5, and the ball milling time is 6h~10h.
[0018] Preferably, the drying process parameters include: the drying equipment is an oven, the drying temperature is 80° C. to 100° C., and the drying time is 6 h to 8 h.
[0019] Preferably, the mixed powder in step 2) is placed in a graphite crucible and compacted.
[0020] Preferably, the graphite crucible has a diameter of 12 mm to 16 mm and a height of 3 mm to 5 mm.
[0021] Preferably, the process parameters of the laser radiation heating in step 2) include: laser power of 180W to 240W, duty cycle of 70% to 100%, heating temperature of 1800°C to 2000°C, and heating time of 5s to 10s.
[0022] A high entropy rare earth ceramic powder is prepared by the above-mentioned rapid preparation method.
[0023] A thermal barrier / environmental barrier coating comprises the high-entropy rare earth ceramic powder.
[0024] An aerospace engine, wherein the surface of the hot end component is covered with the above-mentioned thermal barrier / environmental barrier coating.
[0025] The beneficial effects of the present invention are as follows: the high-entropy rare earth ceramic powder of the present invention has excellent characteristics such as uniform element distribution, no impurity phase, and large synthetic component space, and its preparation method has the advantages of universality, simplicity, rapidity, and high efficiency, and can achieve the purpose of high-throughput screening of materials. It is suitable for use in hot end components of aerospace engines and has a very broad application prospect.
[0026] Specifically:
[0027] 1) The present invention uses laser radiation heating for the synthesis of high-entropy rare earth ceramic powders, and can prepare high-entropy ceramic powders with a huge component space. The preparation method has universal applicability (specifically: a. Powders of various material systems can be synthesized, such as rare earth hafnium salts / zirconates / tantalates / monosilicates / disilicates, etc.; b. Ceramic powders with 9, 10 or even higher components can be synthesized; c. Material systems with complex phase structures, such as β, γ, δ and G phases of disilicates, can also be successfully prepared);
[0028] 2) The high entropy rare earth ceramic powder preparation method of the present invention has the advantages of being simple (simple to operate), rapid (5s to 10s), efficient (capable of high-throughput preparation and performance screening), and stable and controllable process, and is suitable for large-scale promotion and application;
[0029] 3) The high entropy rare earth ceramic powder of the present invention has excellent characteristics such as uniform element distribution, no impurity phase, and large space for synthesizable components. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the temperature rise curve of the mixed powder in Example 1 when it is heated by laser radiation.
[0031] Figure 2 1 is the XRD diagram of the high entropy rare earth ceramic powder in Examples 1 to 3.
[0032] Figure 3 These are the SEM and SEM-EDS images of the high entropy rare earth ceramic powder in Example 1.
[0033] Figure 4 : This is the XRD diagram of the high entropy rare earth ceramic powder in Examples 4-5.
[0034] Figure 5 This is the XRD diagram of the high entropy rare earth ceramic powder in Comparative Example 1. DETAILED DESCRIPTION
[0035] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0036] The particle sizes of Y2O3 powder, Nd2O3 powder, Sm2O3 powder, Eu2O3 powder, Gd2O3 powder, Dy2O3 powder, Ho2O3 powder, Er2O3 powder, Tm2O3 powder, Yb2O3 powder and Lu2O3 powder in Examples 1 to 5 and Comparative Examples 1 to 2 are all 1μm to 3μm, and the purity is ≥99.9%.
[0037] The particle sizes of HfO2 powder, ZrO2 powder, Ta2O5 powder and SiO2 powder in Examples 1 to 5 and Comparative Examples 1 to 2 are all 1 μm to 3 μm, and the purity is ≥99.9%.
[0038] Embodiment 1:
[0039] A high entropy rare earth ceramic powder, the rapid preparation method thereof is as follows:
[0040] 1) 1.4919 g of Dy2O3 powder, 1.5114 g of Ho2O3 powder, 1.5300 g of Er2O3 powder, 1.5917 g of Lu2O3 powder and 8.4195 g of HfO2 powder were added to a ball mill, anhydrous ethanol was used as a medium, the weight ratio of the powder raw material, ZrO2 ball and anhydrous ethanol was controlled to be 1:1.8:1.0, and the mixture was ball milled on a planetary ball mill for 8 h, and the obtained mixed slurry was placed in an oven at 90° C. for 6 h, and then ground and sieved to obtain a mixed powder;
[0041] 2) The mixed powder was placed in a graphite crucible with a diameter of 12 mm and a height of 3 mm, and pressed tightly. The graphite crucible was then fixed on a laser heating table with a clamp, and the laser power was adjusted to 210 W and the duty cycle was 80%. The mixture was heated to 2000 ° C (the heating temperature was tested by an infrared thermometer), and the mixture was kept warm for 5 seconds. The mixture was naturally cooled to room temperature to obtain a high-entropy rare earth ceramic powder (quaternary high-entropy rare earth hafnium salt (Dy 1 / 4 Ho 1 / 4 Er 1 / 4 Lu 1 / 4 )2Hf2O7, denoted as 4-HEREH).
[0042] Performance Test:
[0043] 1) The temperature rise curve of the mixed powder in this embodiment when subjected to laser radiation heating is as follows: Figure 1 shown.
[0044] Depend on Figure 1 It can be seen that the laser heating method is radiation heating, the temperature distribution is more uniform, the temperature of the mixed powder can rise to 2000℃ within a few seconds, and the speed of synthesizing materials is extremely fast.
[0045] 2) The X-ray diffraction (XRD) pattern of the high entropy rare earth ceramic powder (4-HEREH) in this embodiment is as follows: Figure 2 As shown, the scanning electron microscope (SEM) image and energy spectrum element distribution (SEM-EDS) image are as follows Figure 3 shown.
[0046] Depend on Figure 2 It can be seen that the high entropy rare earth ceramic powder is a single RE2Hf2O7 structure, and no other impurities are found.
[0047] Depend on Figure 3 It can be seen that the morphology of high-entropy rare earth ceramic powder is mainly spherical particles with an average particle size of about 300nm. The rare earth elements are evenly distributed without obvious segregation.
[0048] Embodiment 2:
[0049] A high entropy rare earth ceramic powder, the rapid preparation method thereof is as follows:
[0050] 1) 0.9032 g of Y2O3 powder, 1.4500 g of Gd2O3 powder, 1.5301 g of Er2O3 powder, 1.5917 g of Lu2O3 powder and 4.9288 g of ZrO2 powder were added to a ball mill, anhydrous ethanol was used as a medium, the weight ratio of the powder raw material, ZrO2 ball and anhydrous ethanol was controlled to be 1:2.0:1.2, ball milled on a planetary ball mill for 8 h, and then the obtained mixed slurry was placed in an oven at 80° C. for 6 h, and then ground and sieved to obtain a mixed powder;
[0051] 2) The mixed powder was placed in a graphite crucible with a diameter of 14 mm and a height of 4 mm, and pressed tightly. The graphite crucible was then fixed on a laser heating table with a clamp, and the laser power was adjusted to 180 W and the duty cycle was 95%. The mixture was heated to 1900 ° C (the heating temperature was tested by an infrared thermometer), kept warm for 10 seconds, and naturally cooled to room temperature to obtain a high entropy rare earth ceramic powder (quaternary high entropy rare earth zirconate (Y 1 / 4 G 1 / 4 Er 1 / 4 Lu 1 / 4 )2Zr2O7, denoted as 4-HEREZ).
[0052] Performance Test:
[0053] The XRD pattern of the high entropy rare earth ceramic powder (4-HEREZ) in this embodiment is as follows: Figure 2 shown.
[0054] Depend on Figure 2 It can be seen that the high entropy rare earth ceramic powder is a single RE2Zr2O7 structure, and no other impurities are found.
[0055] Embodiment 3:
[0056] A high entropy rare earth ceramic powder, the rapid preparation method thereof is as follows:
[0057] 1) 0.9253 g of Nd2O3 powder, 0.9590 g of Sm2O3 powder, 0.9969 g of Gd2O3 powder, 0.9678 g of Eu2O3 powder and 4.8608 g of Ta2O5 powder were added to a ball mill, anhydrous ethanol was used as a medium, the weight ratio of the powder raw material, ZrO2 ball and anhydrous ethanol was controlled to be 1:2.0:1.2, and the mixture was ball milled on a planetary ball mill for 7 h, and the obtained mixed slurry was placed in an oven at 90° C. for 8 h, and then ground and sieved to obtain a mixed powder;
[0058] 2) The mixed powder was placed in a graphite crucible with a diameter of 15 mm and a height of 4 mm, and pressed tightly. The graphite crucible was then fixed on a laser heating table with a clamp, and the laser power was adjusted to 180 W and the duty cycle was 90%. The mixture was heated to 1800 ° C (the heating temperature was tested by an infrared thermometer), and the mixture was kept warm for 6 seconds. The mixture was naturally cooled to room temperature to obtain a high-entropy rare earth ceramic powder (quaternary high-entropy rare earth tantalate (Nd 1 / 4 Sm 1 / 4 G 1 / 4 Eu 1 / 4 )TaO4, denoted as 4-HERET).
[0059] Performance Test:
[0060] The XRD pattern of the high entropy rare earth ceramic powder (4-HERET) in this embodiment is as follows: Figure 2 shown.
[0061] Depend on Figure 2 It can be seen that the high entropy rare earth ceramic powder is a single RETaO4 structure, and no other impurities are found.
[0062] Embodiment 4:
[0063] A high entropy rare earth ceramic powder, the rapid preparation method thereof is as follows:
[0064] 1) 2.8339 g of Ho2O3 powder, 2.8688 g of Er2O3 powder, 2.9557 g of Yb2O3 powder, 2.9845 g of Lu2O3 powder and 1.8025 g of SiO2 powder were added to a ball mill, anhydrous ethanol was used as a medium, the weight ratio of the powder raw material, ZrO2 ball and anhydrous ethanol was controlled to be 1:1.8:1.2, and the mixture was ball milled on a planetary ball mill for 8 h, and the obtained mixed slurry was placed in an oven at 80°C for 6 h, and then ground and sieved to obtain a mixed powder;
[0065] 2) The mixed powder was placed in a graphite crucible with a diameter of 16 mm and a height of 3 mm, and pressed tightly. The graphite crucible was then fixed on a laser heating table with a clamp, and the laser power was adjusted to 180 W and the duty cycle was 95%. The mixture was heated to 1800 ° C (the heating temperature was tested by an infrared thermometer), and the mixture was kept warm for 6 seconds. The mixture was naturally cooled to room temperature to obtain a high entropy rare earth ceramic powder (quaternary high entropy earth monosilicate (Ho 1 / 4 Er 1 / 4 Yb 1 / 4 Lu 1 / 4 )2SiO5, denoted as 4-HEREM).
[0066] Performance Test:
[0067] The XRD pattern of the high entropy rare earth ceramic powder (4-HEREM) in this embodiment is as follows: Figure 4 shown.
[0068] Depend on Figure 4 It can be seen that the high entropy rare earth ceramic powder is a single X2-RE2SiO5 structure, and no other impurities are found.
[0069] Embodiment 5:
[0070] A high entropy rare earth ceramic powder, the rapid preparation method thereof is as follows:
[0071] 1) 2.2952 g of Er2O3 powder, 2.2673 g of Ho2O3 powder, 2.3153 g of Tm2O3 powder, 2.2381 g of Dy2O3 powder and 2.8841 g of SiO2 powder were added to a ball mill, anhydrous ethanol was used as a medium, the weight ratio of the powder raw material, ZrO2 ball and anhydrous ethanol was controlled to be 1:2.2:1.5, and the mixture was ball milled on a planetary ball mill for 10 h, and the obtained mixed slurry was placed in an oven at 100° C. for 8 h, and then ground and sieved to obtain a mixed powder;
[0072] 2) The mixed powder was placed in a graphite crucible with a diameter of 16 mm and a height of 5 mm, and pressed tightly. The graphite crucible was then fixed on a laser heating table with a clamp, and the laser power was adjusted to 240 W and the duty cycle was 100%. The mixture was heated to 2000 ° C (the heating temperature was tested by an infrared thermometer), and the mixture was kept warm for 10 seconds. The mixture was naturally cooled to room temperature to obtain a high entropy rare earth ceramic powder (quaternary high entropy earth double silicate (Er 1 / 4 Ho 1 / 4 Tm 1 / 4 Dy 1 / 4 )2Si2O7, denoted as 4-HERED).
[0073] Performance Test:
[0074] The XRD pattern of the high entropy rare earth ceramic powder (4-HERED) in this embodiment is as follows: Figure 4 shown.
[0075] Depend on Figure 4 It can be seen that the high entropy rare earth ceramic powder is a single γ-RE2Si2O7 structure, and no other impurities are found.
[0076] Comparative Example 1:
[0077] A high entropy rare earth ceramic powder (denoted as Sample-1) is exactly the same as Example 5 except that the laser radiation heating in step 2) is replaced by muffle furnace calcination (1500° C., 3 h) during preparation.
[0078] Performance Test:
[0079] The XRD pattern of the high entropy rare earth ceramic powder (denoted as Sample-1) in this comparative example is as follows: Figure 5 shown.
[0080] Depend on Figure 5 It can be seen that the high-entropy rare earth ceramic powder prepared by the commonly used solid-phase reaction method contains impurities. The reason is that there are many types of double silicate phases, the most common of which are β, γ, δ and G phases. Phase transitions occur between the phases. When there are many types of rare earth elements or the differences are large, it is difficult to synthesize pure phases using the traditional solid-phase reaction method.
[0081] Comparative Example 2:
[0082] A high entropy rare earth ceramic powder (denoted as Sample-2) is exactly the same as Example 5 except that the "laser power is 240 W, the duty cycle is 100%, and the temperature is heated to 2000°C" in step 2) is adjusted to "laser power is 150 W, the duty cycle is 60%, and the temperature is heated to 1500°C" during preparation.
[0083] Performance Test:
[0084] The XRD pattern of the high entropy rare earth ceramic powder (denoted as Sample-2) in this comparative example is as follows: Figure 5 shown.
[0085] Depend on Figure 5 It can be seen that when the laser power and duty cycle are low, the laser radiation heating temperature is also low. Therefore, the prepared high-entropy rare earth ceramic powder contains more impurities. The reason is that the laser radiation heating temperature is not enough and cannot provide sufficient driving force.
[0086] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for rapidly preparing high entropy rare earth ceramic powder, characterized in that: The following steps are involved: 1) uniformly mixing rare earth oxide powder with one of HfO2 powder, ZrO2 powder, Ta2O5 powder and SiO2 powder to obtain a mixed powder; 2) The mixed powder is subjected to laser radiation heating to obtain high entropy rare earth ceramic powder.
2. The rapid preparation method according to claim 1, characterized in that: Step 1) The rare earth oxide powder is composed of at least four of Sc2O3 powder, Y2O3 powder, La2O3 powder, Nd2O3 powder, Sm2O3 powder, Eu2O3 powder, Gd2O3 powder, Dy2O3 powder, Ho2O3 powder, Er2O3 powder, Tm2O3 powder, Yb2O3 powder, and Lu2O3 powder in an equal molar ratio.
3. The rapid preparation method according to claim 1 or 2, characterized in that: Step 1) The particle sizes of the rare earth oxide powder, HfO2 powder, ZrO2 powder, Ta2O5 powder and SiO2 powder are all 1 μm to 3 μm, and the purity is ≥99.9%.
4. The rapid preparation method according to claim 1 or 2, characterized in that: The molar ratio of the rare earth oxide powder and HfO2 powder in step 1) is 1:2.0-2.2; the molar ratio of the rare earth oxide powder and ZrO2 powder in step 1) is 1:2.0-2.2; the molar ratio of the rare earth oxide powder and Ta2O5 powder in step 1) is 1:1.0-1.1; the molar ratio of the rare earth oxide powder and SiO2 powder in step 1) is 1:1.0-1.1 or 1:2.0-2.
2.
5. The rapid preparation method according to claim 1 or 2, characterized in that: The specific operation of the mixing in step 1) includes wet ball milling, drying and grinding; the process parameters of the wet ball milling include: the ball milling medium is anhydrous ethanol, the ball milling equipment is a planetary ball mill, the weight ratio of the powder raw material, ZrO2 balls and anhydrous ethanol is 1:1.8~2.2:1.0~1.5, and the ball milling time is 6h~10h.
6. The rapid preparation method according to claim 1, characterized in that: Step 2) The mixed powder is placed in a graphite crucible and compacted.
7. The rapid preparation method according to claim 1 or 6, characterized in that: Step 2) The process parameters of the laser radiation heating include: laser power of 180W to 240W, duty cycle of 70% to 100%, heating temperature of 1800°C to 2000°C, and heating time of 5s to 10s.
8. A high entropy rare earth ceramic powder, characterized in that: Prepared by the rapid preparation method described in any one of claims 1 to 7.
9. A thermal barrier / environmental barrier coating, characterized in that: Contains the high entropy rare earth ceramic powder as described in claim 8.
10. An aerospace engine, characterized in that: The surface of the hot end component is covered with the thermal barrier / environmental barrier coating according to claim 9.
Citation Information
Patent Citations
Thermal barrier coating material and preparation method thereof
CN110256092A
High-entropy ceramic powder used for thermal barrier coating and preparation method of ceramic powder
CN110272278A
High-entropy rare earth tantalate ceramic material and preparation method thereof
CN115010491A
High-entropy ceramic material and coating for high-energy electron protection and preparation method of high-entropy ceramic material and coating
CN116606132A
High-entropy rare earth silicate ceramic powder as well as preparation method and application thereof
CN117142854A
Cited By
Multi-element high-entropy silicate ceramic with high ion radius difference and preparation method of multi-element high-entropy silicate ceramic
CN121698649A
High-ionic-radius-difference multi-element high-entropy silicate ceramic and preparation method thereof
CN121698649B